2011
DOI: 10.1111/j.1471-0307.2011.00681.x
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic amines in Iranian white brine cheese: modelling and optimisation of processing factors

Abstract: The simultaneous effects of processing factors such as ripening time (25–75 days), ripening temperature (4–14 °C) and brine concentration (10–13%) on biogenic amines content, proteolysis and sensory score of Iranian white brine cheese were studied, in 12 cheeses. Response surface methodology (RSM) was used to minimise biogenic amines content. At low level of ripening time, biogenic amines content decreased with increasing levels of brine concentration but at high level of ripening time, brine concentration had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In contrast, Aliakbarlu et al . () claim that as their concentration grows, biogenic amines can migrate from white cheese into brine via the concentration gradient. One limiting factor for biogenic amine production (whether in cheese or in brine) is, of course, the sufficient availability of free amino acids to serve as the precursor for the biogenic amines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Aliakbarlu et al . () claim that as their concentration grows, biogenic amines can migrate from white cheese into brine via the concentration gradient. One limiting factor for biogenic amine production (whether in cheese or in brine) is, of course, the sufficient availability of free amino acids to serve as the precursor for the biogenic amines.…”
Section: Resultsmentioning
confidence: 99%
“…The presence and activity of undesirable halotolerant micro‐organisms can lead to the production of substances with toxicological effects, for example biogenic amines (Aliakbarlu et al . ). Biogenic amines (BA) and polyamines (PA) in food arise as a consequence of decarboxylase activity by certain micro‐organisms.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several authors reported that biogenic amine content increased during ripening (Andic, Genccelep, & Köse, ; Buňkova et al, ; Valsamaki, Michaelidou, & Polychroniadou, ). Main biogenic amines were spermine and histamine (Vale & Glória, ), tyramine, cadaverine and putrescine (Novella‐Rodríguez, Veciana‐Nogués, Izquierdo‐Pulido, & Vidal‐Carou, ), tyramine and cadaverine (Andic et al, ), histamine, and cadaverine (Aliakbarlu et al, ) in different varieties of cheese. The type of strain, ripening time, and temperature significantly affected the concentration of biogenic amine ( p < .05).…”
Section: Resultsmentioning
confidence: 99%
“…Yildiz et al () studied biogenic amine contents of Civil cheese collected from retails and they reported that all samples contained one or more different biogenic amines but their levels were not above specified toxic dose for public health. Aliakbarlu, Alizadeh, Razavi‐Rohani, and Agh () investigated the effects of processing factors such as ripening time (25–75 days), ripening temperature (4–14 °C), and brine concentration (10–13%) on biogenic amine content, proteolysis, and sensory scores of Iranian white brined cheese. They reported that the biogenic amine contents decreased at a low‐ripening temperature and high levels of brine concentration.…”
Section: Introductionmentioning
confidence: 99%